Pemanfaatan Kelapa sebagai media Inovasi Masyarakat Pedesaan - Aslinda, Aslinda; Jumadi, Jumadi; Guntur, Muhammad; Kasmita, Maya; Salam, Rudi (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this research is to help the community by conducting training on Coconut Utilization as a medium for Rural Community Innovation. The training was attended by 30 participants obtained from the local community. The training was carried out in two stages, namely: 1) learning and monitoring process, 2) integrated head processing training. In the implementation of the training there were four activities, namely: 1) coconut oil processing unit, 2) shell making, 3) coir fiber fiber processing and 4) coconut juice processing.